Elemental - an arts and ecological reader. - Brady, James; Collins, Tim; Demos, TJ; Douglas, Anne; Fremantle, Chris; Haley, David; Heim, Wallace; Irland, Basia; Little, Ruth; Naidus, Beverly; World of Matter (Gaia Project Press, 2016)
Lyall, John ; Balkin, Amy ; The Otolith Group ; GIAP ; Biemann, Ursula ; Subhankar Banerjee
Kunst en ecologie
boek